Angiogenesis genes, dietary oxidative balance and breast cancer risk and progression: The breast cancer health disparities study. Issue 3 (9th August 2013) - Slattery, Martha L.; John, Esther M.; Torres‐Mejia, Gabriela; Lundgreen, Abbie; Lewinger, Juan Pablo; Stern, Mariana C.; Hines, Lisa; Baumgartner, Kathy B.; Giuliano, Anna R.; Wolff, Roger K.
<x xml:space="preserve">Abstract</x> Angiogenesis is essential for tumor development and progression. Genetic variation in angiogenesis‐related genes may influence breast carcinogenesis. We evaluated dietary factors associated with oxidative balance, DDIT4 (one SNP), FLT1 (35 SNPs), HIF1A (four SNPs), KDR (19 SNPs), MPO (one SNP), NOS2A (15 SNPs), TEK (40 SNPs) and VEGFA (eight SNPs) and breast cancer risk among Hispanic (2, 111 cases and 2, 597 controls) and non‐Hispanic white (1, 481 cases and 1, 586 controls) women in the Breast Cancer Health Disparities Study. Adaptive rank truncated product (ARTP) analysis was used to determine gene and pathway significance with breast cancer. TEK was associated with breast cancer overall (pARTP = 0.03) and with breast cancer survival (pARTP = 0.01). KDR was of borderline significance overall (pARTP = 0.07), although significantly associated with breast cancer in both low and intermediate Native American (NA) ancestry groups (pARTP = 0.02) and estrogen receptor (ER)+/progesterone receptor (PR)− tumor phenotype (pARTP = 0.008). Both VEGFA and NOS2A were associated with ER−/PR− tumor phenotype (pARTP = 0.01 and pARTP = 0.04, respectively). FLT1 was associated with breast cancer survival among those with low NA ancestry (pARTP = 0.009). With respect to diet, having a higher dietary oxidative balance score (DOBS) was significantly associated with lower breast cancer risk [odds ratio (OR) 0.74, 95% confidence interval (CI) 0.64–0.84], with the strongest associations observed for women with the highest NA ancestry (OR 0.44, 95% CI 0.30–0.65). We observed few interactions between DOBS and angiogenesis‐related genes. Our data suggest that dietary factors and genetic variation in angiogenesis‐related genes contribute to breast cancer carcinogenesis.